Antiulcerogenic activity of avipattikar churna on peptic ulcer in experimental rats. - Gautam, Jaya Adhikari, Rashmi Lamsal, Reshma Ghimire, Saurav Lamichane, Shreekrishna (2011)
ABSTRACT: Peptic ulcer is an excoriated area of stomach or intestinal mucosa, resulting due to imbalance between the aggressive factors (acid, pepsin, bile, H. pylori) and the defensive factors (gastric mucous, bicarbonate secretions, prostaglandin, nitric oxide, innate resistance of the mucosal cells. In traditional medicine, many medicinal plants are combined and administered to treat the peptic ulcer as they are rich in active principles and antioxidants. The marketed formulation Avipattikar churna composed of fourteen ingredients which has been used for the treatment of G.I. disorders due to synergistic action. The antiulcerogenic activity of Avipattikar churna was evaluated in pyloric ligated model in rats. Twenty four rats were divided in four groups each containing six rats. Group I, II, III, IV were served as ulcer control, churna low dose (500 mg/kg), churna high dose (750mg/kg) and ranitidine (25mg/kg) group respectively. The gastric contents were collected and evaluated for volume of gastric content, pH, volume of NaOH consumed, acidity, length of ulcer, number of ulcer, gastric irritancy index and curative ratio. In the present study Avipattikar churna was found to have significant antiulcer activity with reference drug ranitidine in pyloric ligation induced gastric ulcers in experimental rats. The test drug reduced the gastric juice volume, acidity, ulcer index and increased the pH of the gastric content. The results were analysed using One-Way ANOVA followed by Dunnett test considering p < 0.01 as level of significance. There were no significant differences on the curative ratio among the treated group which means churna can heal the ulcer in the same extent as ranitidine does. The present finding demonstrated that Avipattikar churna has potent antisecretory and antiulcer effect and justify the usage of this herb to treat peptic ulcer.